Measuring the small scale fishermen's adaptation ability based on their practices: the case of Peninsular Malaysia - Hamdan, Mas Ernawati; Abu Samah, Asnarulkhadi; Idris, Khairuddin; Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2017)
As climate change is worsening, it is apparent that people would manage several adaptation strategies to confront it in the most effective ways. Adaptation practices is crucial, especially among small scale fishermen whose reliance on the weather state is high. This study aims to measure small scale fishermen’s adaptation ability from the angle of their practices. This study is quantitative in nature whereby via a multistage cluster sampling, a total of 200 small scale fishermen were selected as respondent. Findings from this study show Malaysian fishermen’s heavy reliance on fisheries activities, their reluctance to venture into new work fields and low confidence in getting a new job as their main weakness when it comes to their adaptation practices, whereas their ability to diversify their catches and catching tools and their courage to explore new catching areas were seen to be their strength. It is hoped that the discussions from this study be considered in any development plan strategized by concerned parties.